Innovative transdermal drug delivery system based on amoxicillin-loaded gelatin methacryloyl microneedles obtained by 3D printing - GÜNDÜZ, OĞUZHAN (My University, 2023)
© 2023 Acta Materialia Inc.The microneedle (MN) technology platform has a significant potential for enhancing the efficacy of transdermal drug delivery, by using micron-scale arrays with restricted geometries that pierce the skin non-invasively. In this paper, we developed gelatin methacryloyl (GelMA) MNs containing amoxicillin (AMX) as a novel transdermal delivery system using digital light processing (DLP) based 3D printing technology. With the DLP approach, MNs were obtained with high resolution and minimal lead times without geometric limitations. The 3D-printed AMX-loaded GelMA MNs were examined for their morphological, mechanical, swelling and antimicrobial properties as well as the drug release profile. The morphological analysis demonstrated the successful fabrication of the MNs with regular structure and sharp tips. The fabricated MNs displayed good mechanical properties consistent with 0.1 N/needle without breaking. Moreover, the results of the in vitro antibacterial activity assays indicated that AMX-loaded GelMA MNs have significantly inhibited the Staphylococcus aureus and Escherichia coli growth. These findings suggest that the 3D-printed drug-loaded GelMA MNs are a useful platform for transdermal therapeutic delivery and can be developed as a next-generation medical device for managing bacterial infections.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Malzeme Bilimi; Engineering, Computing & Technology (ENG); MATERIALS SCIENCE; Genel Malzeme Bilimi; Fizik Bilimleri; General Materials Science; Physical Sciences; Amoxicillin; DLP 3D printing; Gelatin methacryloyl; Hydrogel; Microneedle; Transdermal drug delivery